2016
DOI: 10.3389/fimmu.2016.00597
|View full text |Cite
|
Sign up to set email alerts
|

ATP-Induced Inflammasome Activation and Pyroptosis Is Regulated by AMP-Activated Protein Kinase in Macrophages

Abstract: Adenosine triphosphate (ATP) is released by bacteria and host cells during bacterial infection as well as sterile tissue injury, acting as an inducer of inflammasome activation. Previous studies have shown that ATP treatment leads to AMP-activated protein kinase (AMPK) activation. However, it is unclear whether AMPK signaling has been involved in the regulation of ATP-induced inflammasome activation and subsequent pyroptosis. In this study, we aimed to investigate this issue in lipopolysaccharide-activated mur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
48
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(54 citation statements)
references
References 61 publications
1
48
0
1
Order By: Relevance
“…4a-d). Extracellular ATP activates the NLRP3-ASC-inflammasome axis leading to secretion of mature IL-1β 36,37 . Ad-infection is associated with sustained autophagy (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…4a-d). Extracellular ATP activates the NLRP3-ASC-inflammasome axis leading to secretion of mature IL-1β 36,37 . Ad-infection is associated with sustained autophagy (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, this is the first study to report PD-induced NLRP3 inflammasome inactivation as a molecular mechanism of mitophagy in SI-AKI. Increasing studies have reported that inflammasome formation-induced activation of pyroptosis plays an important role in inflammatory diseases, including SI-AKI [39][40][41]. In the future, the effects of PD and sirtuins on pyroptosis should be explored further to identify more treatment targets for SI-AKI.…”
Section: Discussionmentioning
confidence: 99%
“…In support of this, it has been deduced that the extent of pyroptosis determines the magnitude of inflammation, and the controlled pyroptosis plays a crucial role in limiting the extent of inflammation and maintains a hemostasis state, as was observed in the early and chronic stage of apical periodontitis. 15 Further, a study by Zha et al (2016) also reported that inflammasome activation was enhanced in metformin-treated mice upon bacterial infection. 19 Moreover, our observations revealed a strong and positive correlation of AMPK⍺(T172) with NLRP3 levels in the metformin group.…”
Section: Discussionmentioning
confidence: 97%
“…15 Further, a study by Zha et al (2016) also reported that inflammasome activation was enhanced in metformin-treated mice upon bacterial infection. 19 Moreover, our observations revealed a strong and positive correlation of AMPK⍺(T172) with NLRP3 levels in the metformin group. Based on these findings, enhanced NLRP3 expression and increased mitophagy could be attributed to the metformin-induced increased AMPK phosphorylation, as AMPK activation indirectly or directly regulates the phosphorylation of NLRP3 and mitophagic proteins.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation